Household/Stakeholders Knowledge, Attitudes and Practices Towards Conservation, Protection, and Sustainable Management of Mt. Malindang Range Natural Park, Philippines - Villanueva, Grace V.; Calago, Jersam C.; Alaman, Bobby B.; Mapi-ot, Emmarie; Villantes, Yunalyn L; Galindo, Russel (East Asian Journal of Multidisciplinary Research, 2024)
This study assesses the knowledge, attitudes, and practices (KAP) of households surrounding the park in the province and sustainable management of Misamis Occidental, Philippines, regarding the sustainable management, conservation, and protection of MMRNP. The study covers seven municipalities and three cities benefiting from MMRNP's water ecosystem services. A total of 1,875 respondents were interviewed face-to-face from July to September 2023. Statistical tests were performed using STATA version 17. The findings disclosed that most of the respondents are female, married, with several educational backgrounds and employment status. However, the average residency of age is high, indicating a long-term connection to the park. The economic heterogeneity observed in monthly income emphasizes the importance of considering socioeconomic factors in conservation strategies, plans, and programs.